Solution heat treatment of gas-atomised aluminium alloy powder for cold spray - Sabard, Alexandre (2020)
Cold gas dynamic spraying, or cold spray, is a deposition technique exploiting the kinetic energy of fine powder particles to achieve a dense coating on a target substrate surface. The aim of this research project is to develop the solution heat treatment of aluminium alloy powder to optimise cold spray for structural repair applications. Metallic powders used for cold spray deposition are generally manufactured using gas-atomisation. In the case of aluminium alloys, it has been shown that the rapid solidification experienced by gas-atomised powders generally leads to non-equilibrium microstructure due to the high cooling rates (up to 108 K.s−1 ). The solute segregation associated with this microstructure leads to inconsistency in the powder composition and is detrimental in terms of reproducibility and response to heat treatment. In order to reduce this segregation and obtain more control of the powder microstructure, solution heat treatment was considered in the scope of this study. Solution heat treatment consists of a process of heating a material below its melting temperature for a specific time within the single-phase region in order to allow atoms to diffuse evenly throughout the aluminium matrix. In this study, the microstructural modification associated with such a process was characterised for two different Al alloys : Al 7075 and Al 6061. The powders cross section were characterised by Scanning Electron Microscopy (SEM), Electron backscatter diffraction (EBSD) to evaluate the effects of such treatment. It was found that the non-equilibrium microstructure of powders following gas-atomisation was homogenised, and that the majority of solute atoms were dissolved back in the aluminium matrix. A higher consistency in microstructure was observed throughout the powder particles compared with the asreceived powder, meaning that a relative control over the particles microstructure was gained through heat treatment. The ageing and precipitation kinetics of the homogenised powders was monitored and measured using techniques such as Differential Scanning Calorimetry. A development of precipitates through exposure at room temperature following solution heat treatment was characterised, resulting in a microhardness increase of 80% in 20 days in the case of Al 7075. The solution heat-treated powders were subsequently sprayed onto Al alloys substrates, to evaluate the effect of such heat treatment of their behaviour upon cold spray deposition. Solution heat treated powder were cold sprayed using both He and N2 as a carrier gas. In both cases, the enhanced deformability of the heat treated powders led to a large increase in deposition efficiency and resulting coating thickness compared with the as-received powder. An increase from 5% to 22% was measured in the case of Al 7075, showing a substantial improvement in ability to deposit the powder particles. This was attributed to a precipitate dissolution and more homogeneous microstructure, facilitating the particle deformation upon impact. As the microhardness of the heat-treated Al 7075 powder increased due to ageing, it was found that their deposition efficiency during cold spray decreased. Particles following solution heat treatment and quench (SHT+Q) experienced a 25.5 ± 3.6% DE, while T6 powder particles were sprayed with 6.8 ± 0.3 % DE. This was attributed to a change in the kinetic energy required to deform the particles upon impact. As the deposition efficiency decreased, the ratio of rebounding particles increased, resulting a more important tamping effect, compressing deposited particles throughout the cold spray deposition process. Bond and cohesion strength of the deposited coatings were measured, both increasing as the powder was aged further. Cohesion strength was measured at 224 ± 11 MPa for the coatings sprayed using SHT+Q powders, whereas the coatings sprayed using T6 powder reached values up to 510 ± 10 MPa. An inverse linear relationship was measured between the deposition efficiency and the cohesion strength of coatings, highlighting the importance of the tamping effect in cold spray deposition of Al alloys.